ANALISIS FAKTOR PENGHAMBAT SKRIPSI MAHASISWA JURUSAN PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS WIJAYA KUSUMA SURABAYA - Pratiwi, Desi Eka; Roosyanti, Anna (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2019)
This study aimed to describe the inhibiting factors for the completion of Elementary Education Teacher students’ bachelor thesis (hereinafter will be called PGSD Students) in terms of internal and external factors. This research is qualitative descriptive using mixed method approach. The data of this research were collected using questionnaire and interview. The data analysis was performed by counting the percentage from frequent number that emerge in the questionnaires, then describes. The collected data were grouped and presented so that it can be easy top read, then analyzed and concluded using percentage technique. The result of this study showed that (1) The highest obstacle experienced by students in completing a thesis is psychological barrier with cognitive sub-indicator, it has 62 voters with percentage 67,39%; (2) The lack of books or references with 61 voters with a percentage of 66.30%; (3) physical barriers with pain sub-indicator were chosen by 60 voters with a percentage of 65.21%; (4) psychological barriers with affective sub indicator has the number of voters as many as 57 with a percentage of 61.95%; (5) counseling problems with a total of 55 voters with a percentage of 59.78; (6) meeting with supervisors problem were chosen by a total of 52 voters with a percentage of 56.52%; (7) Psychic or mental obstacle problems with psychomotor sub-indicators with 50 voters with a percentage of 54.34%; (8) the costs / funds problems with a total of 49 voters with a percentage of 53.26%; (9) on-campus activities with a total of 46 voters with a percentage of 50%; (10) problems with off-campus activities and the influence of parents with a total of 39 voters with a percentage of 42.39%; (11) pregnancy problems with 37 voters with a percentage of 40.21%; (12) family problems with 27 voters with a percentage of 29.34%. Based on the results of the analysis above, it is expected to be an evaluation material